Creep Effects in the Finite Element Analysis of Thermo-Mechanical Problems - T. Niezgoda (Engineering Transactions)
A finite element method is employed to analyse creep of a structure under mechanical and thermal load. Theoretical considerations are illustrated by a numerical test in which the effect of temperature on the stress relaxation is analysed.